Synthesis, characterization and VOCs adsorption kinetics of diethylstilbestrol-substituted metallophthalocyanines - (:unkn) unknown (WORLD SCI PUBL CO INC, 2019)
Compound (4,4'-hex-3-ene-3,4-diyl)bis(4,1-phenylene)bis(oxy)diphthalonitrile 3 was synthesized by the reaction of 4-nitrophthalonitrile 1 and diethylstilbestrol 2 in dry DMF in presence of dry K2CO3 . New mononuclear phthalocyanines 4-6 were obtained from compound 3 by addition of the corresponding metal salts [Co(OAc)(2)center dot 4H(2)O, Zn(OAc)(2)center dot 2H(2)O and Cu(OAc)(2)]. The novel compounds were characterized by elemental analysis and FT-IR, UV-vis, H-1-NMR and MALDI-TOF mass spectroscopy techniques. The effects of four main groups of organic vapors on these novel compounds were studied and discussed. The adsorption kinetics of alkanes (n-hexane and n-octane), alcohols (methanol and 2-proponal), chlorinated hydrocarbons (dichlommethane and trichloromethane) and amines (diethylamine and triethylamine) on 4-6 were examined using three adsorption kinetic models: the Elovich equation, the pseudo-first-order equations and Ritchie's equation. Results show that the linear regression analysis with respect to the pseudo-second-order rate equations generates a straight line that best fits the data of adsorption of alcohols and chlorinated hydrocarbons on Pc films. On the other hand, the Elovich equation generates a straight line that best fits the data of adsorption of alkanes and amines.
Keywords: phthalocyanine; mononuclear; adsorption kinetics; amines; alkanes; PHTHALOCYANINE THIN-FILMS; GAS-SENSING PROPERTIES; COPPER PHTHALOCYANINE; ELOVICH EQUATION; COMPLEXES; ELECTROCHEMISTRY; COBALT; HOMO